Photojournalism as political encounter: western news photography in the 2015 migration 'crisis'. (August 2019) - Chouliaraki, Lilie; Stolić, Tijana
In this article, the authors analyse the news photojournalism of the 2015 European migration 'crisis' as a political encounter between western publics and arriving migrants, where the latter are not simply 'the represented' but people who act within the photographic space. Inspired by Azoulay's view of photography as 'civic duty', where 'those represented continue to be present there at the time they are being watched in the photograph' and, in so doing, actively call for a response from their publics, the authors ask the question of who acts and how as well as what bonds of civic duty such action puts forward for those publics. At the heart of these questions on agency lies a conception of arriving migrants as specifically vulnerable actors – people whose very precarity becomes a resource for meaningful action. This visual analysis of front-page news images across nine western countries, (84 images in June–November 2015) demonstrates that their photojournalism of migration enables two types of political encounters with arriving migrants: 'action on migrants', where migrants are mainly acted upon within the procedural encounters of border institutions, and 'action by migrants', where migrants act upon and affect others within existential encounters that can potentially touch upon people's emotional and activist sensibilities. While, in line with the canons of photography and migration studies, both types of political encounters restrict precarious agency within the binary positions of victimhood and threat, it is the latter, 'action by migrants' that has the potential to break with such binaries and cast vulnerability as resistance – as deliberate exposures of the body to the power of the border, which present migrants as political actors in activist practices of transnational solidarity.